Role of Phonetics and Spelling in LOLspeak - Mrázová, Michaela (Univerzita Pardubice, 2013)
The aim of this thesis is to provide an insight into LOLspeak (an internet language used by people to create funny pictures of cats) and to investigate a relation between phonetics and spelling in forming LOLspeak. First, aims of this thesis and a hypothesis are established. Next, a brief introduction to the world of LOLspeak is given. Definitions of key linguistic terms and phenomena, such as phoneme, grapheme, ortoghraphy, or inflectional -s, follow afterwards. Description of methods of data gathering and their analysis, followed by the presentation of findings of said analysis, is given in the next part. Confirmation or refutation of previously established hypothesis along with a brief summary of findings is provided in the conclusion of this thesis.
Role fonetiky a spellingu v LOLspeaku
Keywords: LOLspeak; phonetic transcription; plural; present tense; phoneme; spelling; internet slang; silent e; inflection; grapheme; LOLspeak; fonetická transkripce; množné číslo; přítomný čas; foném; pravopis; internetový slang; nevyslovované e; skloňování; grafém